Parámetros Para La Identificación Y Aplicación Sostenible De Vis Multifamiliar En La Ciudad De Ibagué No/Vinss (2022)
The growth of the urban area of ​​the city of Ibagué from the 20th century has been characterized by disorganized urbanism, the result of the growing activity of informal settlements, by people who came from the rural area of ​​Tolima, has mid-50s. Settlements began to be generated rapidly and progressively in the urban area in a linear way on the roads to Honda and Bogotá. This growth of the city generated a gap between communes 7,8 and 9 where the absence of facilities thanks to the development of housing projects that do not take into account the indicators of sustainability, thus generating a disconnection with the rest of the city.